Beyond the Norm: Primary Paravertebral Hydatidosis – A Puzzling Presentation - Akshi Raj; Madhuri Singh; Shirish Sahebrao Chandanwale; Anuj Sharma; Kumar Roushan (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Hydatid disease is a zoonotic infection endemic in farming areas but occurs worldwide. It most commonly involves the liver, followed by the lungs, kidney, spleen, brain, and bones. Isolated primary paravertebral hydatid cyst is extremely rare and has been reported to constitute less than 1% of cases of hydatidosis. The rarity may pose a diagnostic challenge for clinicians, especially in nonendemic areas. A high index of suspicion is therefore necessary as its differential diagnosis can range from chronic hematoma and lipoma to malignant soft tissue tumors. Various imaging techniques such as ultrasound, computed tomography scan, and magnetic resonance imaging can aid in diagnosing the condition; however, histopathological correlation remains essential. In this case report, we detail an uncommon occurrence of a hydatid cyst found exclusively within the paravertebral location presenting as a slow-growing asymptomatic mass in the back, posing a clinical diagnostic dilemma.